Measuring e-insurance in Greece: the case of public insurance funds - Mouchakis, Dimitrios; Drosos, Dimitrios (SPOUDAI Journal of Economics and Business, 2009)
Everyday, millions of people use Internet for communication, for access in information, for research, for doing businesses and for education. Almost every organization promotes his presence in the Web, so that its content and activities made available. Despite the widest usage of Internet, it is still open the question of benefit and determination, in sufficient degree, on the disposal of information. Even though a lot of systems and methods have been proposed and implemented for the general evaluation of web sites, these are still of limited value in assessing the quality of the content. The main reason is that the type of content can vary from one website to another. The scope of our research is the analysis and the comparative evaluation of the public insurance funds websites in Greece. The selection of the research sample was based on 22 public insurance funds that had a valid link to their website. In order of analyzing and assessing the websites content, a model checklist with eight broad homogenous criteria groups was used. The results are disappointing as only one fund was found above the average in overall evaluation, actually having a value approximately 2 times over the second fund. As a result, e-government in Greece in the sector of e-insurance is far from meeting the demand of relative services from the citizens and enterprises. JEL Classifications: G23, O32, L86